Mariborska škofija in (de)nacionalizacija cerkvenega premoženja - Ščavničar, Darko (Dileme, 2025)
Based on studying archival sources and literature, the author explores the implementation of nationalization after the Second World War, which enabled the communist authorities to destroy what private property the Church had left after the agrarian reform. Thus, by 1960, about half of all nationalized religious buildings in Slovenia were located in the then Diocese of Maribor. This percentage of nationalized religious buildings was definitely a severe blow to the aforementioned diocese in pastoral, educational, and, last but not least, economic terms. The second part of the article focuses on an analysis of the process of denationalizing the property taken from the Archdiocese of Maribor in the past. In particular, the author discusses the process of the restitution of this property, as exemplified by the theological seminary at Vrbanska cesta 30 in Maribor, which was returned to the ownership of the archdiocese in full, which restored the legal and economic basis of this ecclesiastical institution. He also highlights the historical context and the legal and societal implications of this important step.
Keywords: agrarian reform; agrarna reforma; Communist Party; Diocese of Maribor; Državno lastništvo; Katoliška cerkev; komunistična partija; Privatizacija; Škofija Maribor